Peran Employee Green Behavior terhadap Green Teacher Performance dalam Lingkungan Madrasah Kota Medan dengan Pendekatan Organizational Ambidexterity dan Green Self-Efficacy - Manda Dwipayani Bhastary; Amin Hou; Thomas Sumarsan Goh; Nasib Nasib; Wily Julitawaty (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study examines the influence of employee green behavior on the performance of green instructors in the Madrasah context in Medan City, using the frameworks of organizational ambidexterity and green self-efficacy. Adopting a quantitative research methodology, the study utilized surveys as the primary data collection tool. The research population consisted of all Madrasah instructors in Medan City, totaling 229 individuals, who also served as the research sample. Data analysis was conducted using quantitative statistical methods, specifically path analysis. Primary data were collected through surveys, while secondary data were obtained from official Madrasah records. The findings reveal that instructors’ green self-efficacy in Madrasahs in Medan City is significantly influenced by their green behavior. Moreover, environmentally sustainable practices positively impact organizational ambidexterity, which in turn affects teacher performance. However, organizational ambidexterity does not have a direct significant influence on green teacher performance. Conversely, employee green behavior indirectly enhances teacher performance through its effects on organizational ambidexterity and green self-efficacy.